Along the Santa Fe Trail (Raton, NM, 1953)
These are three broadcasts given under the name "Along the Santa Fe Trail". Only one manuscript is marked "written by Marion Blackwell Yoder", it is unclear if she wrote them all or not. The December 6 broadcast seems to be an introduction to the Sunday program (as well as an advertisement for the El Portal Hotel, Sponsor); the Dec. 20 gives various tales concerning happenings and history in Raton and along the trail and mentions using writings by Kenneth Fordyce; the December 27th issue gives the family history of Mrs. Yoder.
Article written by local people
Master list item #: 18
File location is in the Raton File Cabinet
Keywords: Howe, G.A.; Stanley; Conway, Jay; Menzer, Gus; Fordyce, Kenneth; Ferguson, Mernard; Birch, Tommy; Lott, Agnes C; Glass, Oceola; Merrill, Laura Stockton; Stockton, Mathias B. "Thike"; W.P.A. "The Writers Project"; El Portal; Stockton Ranch; Local History; Life and Customs; Hangings; Tragedy; Raton, New Mexico; Santa Fe Trail; Raton Pass; Cimarron, New Mexico; Kit Carson